2020
DOI: 10.1186/s12885-020-6535-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of radiotherapy techniques on the plan quality and on the risk of secondary tumors in patients with pituitary adenoma

Abstract: Background: This planning study compares different radiotherapy techniques for patients with pituitary adenoma, including flatness filter free mode (FFF), concerning plan quality and secondary malignancies for potentially young patients. The flatness filter has been described as main source of photon scatter.Material and methods: Eleven patients with pituitary adenoma were included. An Elekta Synergy™ linac was used in the treatment planning system Oncentra® and for the measurements. 3D plans, IMRT, and VMAT p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Following the discovery of X-rays, it was found that frequent exposure experienced by physicians increased their risk of developing cancer (13)(14)(15)(16)(17)(18). Studies on atomic bomb survivors (19)(20)(21)(22)(23)(24) and patients with cancer receiving radiation therapy (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) have found that the risk of tumorigenesis is associated with acute or fractionated high-dose radiation exposure. although opinions differ as regards the harm of low-dose radiation to the human body, the impact of low-dose radiation on cancer risk has gained scientific attention.…”
Section: Introductionmentioning
confidence: 99%
“…Following the discovery of X-rays, it was found that frequent exposure experienced by physicians increased their risk of developing cancer (13)(14)(15)(16)(17)(18). Studies on atomic bomb survivors (19)(20)(21)(22)(23)(24) and patients with cancer receiving radiation therapy (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) have found that the risk of tumorigenesis is associated with acute or fractionated high-dose radiation exposure. although opinions differ as regards the harm of low-dose radiation to the human body, the impact of low-dose radiation on cancer risk has gained scientific attention.…”
Section: Introductionmentioning
confidence: 99%
“…Data on SC in the brain originates mainly from paediatric cohorts treated with cranial radiotherapy, where excess odds ratios (EOR) of 0.33 and 0.079 per Gy have been reported for gliomas and 1.06 and 5.1 per Gy for non-malignant and malignant meningiomas by the North American and British Cancer Survivor Study respectively [20] . Different photon techniques have been shown to have a theoretical impact on the risk of secondary tumours [21] . The rapid distal dose fall-off of protons may significantly reduce the integral dose and thus reduce the risk of SC.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few investigations using model calculations have been published about the impact of the FFF mode on SMR. Besides works about patients with breast cancer, 11 ependymoma, 12 and pituitary adenoma 13 there is only one paper evaluating the SMR for patients with prostate cancer treated with linacs with and without flattening filter 14 which confined to only three patients at cost of statistical significance. Additionally, they used another therapy planning system (TPS) which can affect the out‐of‐field dose 15 …”
Section: Introductionmentioning
confidence: 99%